MATERIALITY AND SPIRITUALITY IN BALI TOURISM: AN ETHICAL REFLECTION ON THE TRI-HITA-KARANA - Ida Bagus Putu Suamba; I Ketut Sutama (Jurnal Internasional Ilmu Pengetahuan Terapan bidang Pariwisata dan Events, 2017)
This paper aims at finding out ethical drawbacks the concept Tri-hita-karana has in its pragmatic level and offer an insight of critical analysis of ethical values. Tri-hita-karana has been seen as the foundation on which Bali Tourism developed to its full range. The methods of study used are library and field researches focusing on the ontological, axiological, and pragmatic levels in Bali tourism. It has found that the significant gain in the field of materiality, spirituality tends to be marginalised and vice-versa. This has further impact on life of Balinese. Imbalance of relationships exists between human beings and their fellows, human beings and nature, and human beings and divinity. Nevertheless, both domains are required in life, and any of these is absent, life is just impossible since life is the permutation of them in complex ways. Materiality gains seem to bring Balinese away from spirituality vis-a-vis religion in its right sense. Of the ethical perspective, the Tri-hita-karana as the philosophical foundation of tourism in Bali provides ideas/thoughts that can be used to minimalize the gaps because it does not lay down ethical outlook as how to cope with the gaps. The relationship amongst those elements involved is basically a matter of ethics as philosophy of moral, and hence ethical consideration is required in designing as well as in implementing policy in tourism. Critical ideas are required for not only of metaphysical perspective but also of ethical values and pragmatic practices. Bali tourism tends to dehumanize Balinese if not immediate ethical considerations of Tri-hita-karana are taken into account in pragmatic levels. Development and sustainability of Bali Tourism should be based on Balinese cultural spirit and values; looking it from its inner strengths.